2012
DOI: 10.1186/1756-0500-5-107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suitable reference genes for gene expression studies in porcine alveolar macrophages in response to LPS and LTA

Abstract: BackgroundTo obtain reliable quantitative real-time PCR data, normalization relative to stable housekeeping genes (HKGs) is required. However, in practice, expression levels of 'typical' housekeeping genes have been found to vary between tissues and under different experimental conditions. To date, validation studies of reference genes in pigs are relatively rare and have never been performed in porcine alveolar macrophages (AMs). In this study, expression stability of putative housekeeping genes were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 43 publications
(120 reference statements)
3
47
0
Order By: Relevance
“…The use of reference genes which have a stable expression between the compared groups is crucial for gene expression investigation (Nieto et al, 2009;Cinar et al, 2012). Previous studies have shown that different reference genes can modify the outcome and conclusions of a specific study (Glare et al, 2002;Dheda et al, 2004;Kriegova et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The use of reference genes which have a stable expression between the compared groups is crucial for gene expression investigation (Nieto et al, 2009;Cinar et al, 2012). Previous studies have shown that different reference genes can modify the outcome and conclusions of a specific study (Glare et al, 2002;Dheda et al, 2004;Kriegova et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The NF is calculated from two or more genes with the variable V as the pairwise variation (V n /V n +1) between two sequential normalization factors (NF n and NF n +1). We applied the default threshold (0.15) as a cut-off [7]. If the calculated NF is less than 0.15, additional reference genes are not necessary.…”
Section: Resultsmentioning
confidence: 99%
“…However, more and more evidence suggests that expression of some commonly accepted reference genes, such as glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) and beta actin ( ACTB ), are affected by experimental and clinical conditions; therefore, they may not always be suitable controls for normalization [710]. Leading qPCR investigators have suggested that reference genes must be validated for each experimental situation to acquire meaningful data [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven genes (ACTB, GAPDH, B2M, TBP, RPL4, TOP2B, HMBS, HPRT1, SDHA, YWHAZ, and PPIA) were selected (Table 1) for stability analysis [24] [25] [26] [27]. The specific primers of ADSL, AMPD1, and ATIC were designed using Primer Premier 5.0 software ( Table 2) …”
Section: Primer Design and Synthesis And Real-time Pcrmentioning
confidence: 99%